Oral Tolerance Induced by Transfer of Food Antigens via Breast Milk of Allergic Mothers Prevents Offspring from Developing Allergic Symptoms in a Mouse Food Allergy Model - Takeshi Yamamoto; Yuma Tsubota; Toshihisa Kodama; Natsuko Kageyama-Yahara; Makoto Kadowaki (Clinical and Developmental Immunology)
We examined whether maternal exposure to food antigens during lactation and maternal allergic status would affect the development of food allergy in offspring. OVA-sensitized or OVA-nonsensitized BALB/c female mice were exposed or unexposed to OVA during lactation. After weaning, their offspring were systemically sensitized twice with OVA and repeatedly given OVA by oral intubation. While 97.1% of the mice breastfed by OVA-nonsensitized and OVA-unexposed mothers developed allergic diarrhea, 59.7% of the mice breastfed by OVA-exposed nonallergic mothers during lactation and 24.6% of the mice breastfed by OVA-exposed allergic mothers during lactation developed food allergy. Furthermore, OVA was detected in breast-milk from OVA-exposed nonallergic mothers during lactation (4.6±0.5 μg/mL). In addition, OVA-specific IgG1 titers were markedly increased in breast milk from allergic mothers (OVA-sensitized and OVA-unexposed mother: 11.0±0.5, OVA-sensitized and OVA-exposed mother: 12.3±0.3). Our results suggest that oral tolerance induced by breast milk-mediated transfer of dietary antigens along with their specific immunoglobulins to offspring leads to antigen-specific protection from food allergy.